Neuroleptic malignant syndrome. Issue 8 (August 1986) - Moore, A; O'Donohoe, N V; Monaghan, H
Abstract : A case of the neuroleptic malignant syndrome, an idiosyncratic response to neuroleptic drugs, is described. Symptoms persisted for eight weeks. The stopping of neuroleptics and general supportive measures are the mainstay of treatment. Failure to recognise this syndrome can lead to morbidity and death.